1989
DOI: 10.1080/03014468900000162
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of group-specific component (Gc) subtypes in several Mongoloid populations of East Asia

Abstract: The distribution of group-specific component (Gc) subtypes was determined by isoelectric focussing in thin layer polyacrylamide gels of pH range 4 to 6.5, in a group of 2412 individuals from 10 Mongoloid populations of East Asia. The sample comprised 959 Chinese from different localities (Singapore, 249; Malaysia, 347; Taiwan, 246; Hong Kong, 57; Fuzhou mainland, 60), 338 Koreans, 277 Filipinos, 484 Thais, 330 Malays and 24 Indonesians. The Filipinos and Malays had lower frequencies of Gc2 (0.15 and 0.18) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…The frequencies of Gc lr have been found to range from 0.30 to 0.35 which falls within the reported frequencies of the allele in the Mongoloid population of eastern India (Saha, 1987a;Walter et al, 1986). The Mongoloid population of South East Asia, the Chinese and Japanese have much higher frequencies of Gc ~F (Saha, 1989a). The frequencies of Gc is varied from 0.35 to 0.38 which are in agreement with the reported frequency of Gc Is in the Mongoloid population of eastern India.…”
Section: Serum Proteinssupporting
confidence: 77%
“…The frequencies of Gc lr have been found to range from 0.30 to 0.35 which falls within the reported frequencies of the allele in the Mongoloid population of eastern India (Saha, 1987a;Walter et al, 1986). The Mongoloid population of South East Asia, the Chinese and Japanese have much higher frequencies of Gc ~F (Saha, 1989a). The frequencies of Gc is varied from 0.35 to 0.38 which are in agreement with the reported frequency of Gc Is in the Mongoloid population of eastern India.…”
Section: Serum Proteinssupporting
confidence: 77%
“…In addition, a detailed study on blood genetic markers has been reported in the minority Koreans in mainland China by Goedde et al (19841, Yuan et al (1984), and Xu et al (1986). Recently our laboratory reported on the distribution of transferrin, group-specific component subtypes, a,-protease inhibitor, alpha-1-P-glycoprotein, and red cell phosphoglucomutase subtypes in Koreans, in connection with population genetic studies of several Mongoloid populations of East Asia (Saha, 1987(Saha, , 1988(Saha, , 1989a(Saha, ,b, 1990Juneja et al, 1989). The data on these systems have been incorporated within and reconstituted as a larger sample in the present investigation.…”
mentioning
confidence: 98%
“…The gene frequency of GclF observed in the Oraons of Bihar (0.3829) and Jalpaiguri (0.2953) appears to be much higher than in the other tribal groups of South India (0.082-0.23; Walter et al, 1984;Kamboh and Kirk, 1984). However, the Mongoloid tribes of Assam and East Asia have been reported to have a similar high frequency of GclF (Walter et al, 1986;Saha, 1988a).…”
Section: Haemoglobin and G6pdmentioning
confidence: 57%
“…Tamil Hindus sampled in Singapore have a frequency of 0.305 for GclF (Saha, unpublished). A high frequency of GdlF is, in general, typical of mongoloid and negroid populations (Saha, 1988a). There is an excess of homozygotes at the Gc locus in both the samples of Oraons (X,z = 3.335; P = >0.05 and 5.24; P = <0.025 respectively).…”
Section: Haemoglobin and G6pdmentioning
confidence: 97%